Students’ critical thinking ability in analyzing descriptive paragraph - Patahuddin Patahuddin; Syawal Syawal; Amri Amri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Learning that is oriented to the development of critical thinking skills is one of the main priorities of an educator in their learning activities. This study aims to analyze students' critical thinking skills in analyzing a descriptive paragraph. This study uses a descriptive method with a quantitative approach. This research will be carried out during the odd semester of the academic year 2021/2022. The subjects of this study were all 1st-semester students in the English language education study program FKIP UMPAR which consisted of 18 students. The research instruments are observation and interview which involves the descriptive paragraphs observation and the interview guide sheet. Data analysis using descriptive statistical analysis. Referring to the data gained in the study, the researcher found that the critical thinking ability of students to analyze a descriptive paragraph was still very low. It was discovered that students' critical thinking skills in analyzing descriptive paragraphs were in a low category, students achieving a score below the minimum graduation standard set by the university. The data is also reinforced by the results of interviews which show that students are not accustomed to doing English paragraph analysis.